2017
DOI: 10.1016/j.celrep.2017.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking-Mediated STING Degradation Requires Sorting to Acidified Endolysosomes and Can Be Targeted to Enhance Anti-tumor Response

Abstract: SUMMARY STING is an ER-associated transmembrane protein that turns on and quickly turns off downstream signaling as it translocates from the ER to vesicles. How STING signaling is attenuated during trafficking remains poorly understood. Here, we show that trafficking-mediated STING degradation requires ER-exit, function of vacuolar ATPase complex, and late stage STING vesicles are sorted to Rab7-positive endolysosomes for degradation. Based on analysis of existing structures, we also identified the helix aa281… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
212
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(243 citation statements)
references
References 22 publications
29
212
2
Order By: Relevance
“…Of the non-kinase inhibitors, we were intrigued by both bafilomycin and concanomycin, which blocked pathway activation at low doses, but unexpectedly potentiated pathway activity at higher doses. We did not delve into this further, but note that a recent report (27) implicated a negative regulatory role of ATP6V1A, consistent with our finding.…”
Section: Resultssupporting
confidence: 90%
“…Of the non-kinase inhibitors, we were intrigued by both bafilomycin and concanomycin, which blocked pathway activation at low doses, but unexpectedly potentiated pathway activity at higher doses. We did not delve into this further, but note that a recent report (27) implicated a negative regulatory role of ATP6V1A, consistent with our finding.…”
Section: Resultssupporting
confidence: 90%
“…Further, within the STING Western blot and the IFNβ mRNA data, there is an interesting and hypothesis‐generating tissue‐specific finding. It is known that intracellular trafficking and proteasomal degradation regulate activated STING levels . We noted that mice ‘l’, ‘m’ and ‘n’ exhibited differential levels of STING in splenocytes versus lung cells in the Western blot, and versus control mice ‘j’ and ‘k’ in lung cells.…”
Section: Discussionmentioning
confidence: 90%
“…Immunofluorescent microscopy has shown that, at later time points, STING co‐localizes with Rab7‐containing vesicles (late endosome/lysosome) but not vesicles containing Rab5 (early endosome) or Rab11 (recycling endosomes). Inhibiting lysosomal function by blocking acidification prevents activation‐induced STING degradation . To prevent chronic cGAS activation, the STING pathway also induces autophagy and this is thought to help clear cytosolic DNA.…”
Section: Basic Biology Of the Sting Pathwaymentioning
confidence: 99%
“…Thus, cytosolic DNA initiates a cGAS‐STING‐TBK1‐IRF3 signaling cascade that induces a type I IFN response, and signaling becomes resolved by degradation of components of the STING pathway as well as clearance of the stimulatory DNA . There are many post‐translational modifications of both cGAS and STING that regulate their function and allow cross‐talk of the STING pathway with other cellular processes.…”
Section: Basic Biology Of the Sting Pathwaymentioning
confidence: 99%
See 1 more Smart Citation